A Framework for Heritage-Led Regeneration in Chinese Traditional Villages: Systematic Literature Review and Experts’ Interview - Yang Yang; Hazwan Ariff Hakimi; Nur Farhana Azmi; Kaiyi Li; Bingyu Duan (Heritage, 2025)
With rapid urbanization and modernization, the deterioration of historical areas has become an increasing concern. While heritage-led regeneration has proven effective, most studies have focused on urban contexts. Rural traditional villages, particularly in developing countries such as China, face even greater challenges and remain understudied. This study addresses this gap by developing a framework for heritage-led rural regeneration, grounded in community-building theory and highlighting heritage capacity as a key driver of village revitalization. Using a two-round systematic literature review, 64 papers from Web of Science and Scopus were analyzed to construct the framework. It consists of two levels: a preliminary framework identifying five key dimensions—public participation, media platform construction, adaptive reuse, heritage industry development, and landscape maintenance—and an integrated framework further detailing 13 sub-dimensions within these areas. Expert interviews were then conducted to validate the framework and examine its practical implementation challenges and future development directions. This framework integrates community-building theory with heritage-led regeneration, offering both theoretical insights and practical guidance for revitalizing traditional villages in China and beyond.